Craniocervical posture in children with class I, II and III skeletal relationships (2017)
Objective: To describe the characteristics of craniocervical posture of children aged between 6 and 11 years and its relationship to their sagittal skeletal classification. Material and Methods: This descriptive cross-sectional study involved 107 children (55 girls - 52 boys), aged between 6 and 11 years. The sample included no previous orthodontically/orthopedic treated and systemically healthy children. After proper calibration, lateral skull radiographs, taken for diagnosis purpose for maxillary orthopedic treatment, were obtained by the same operator in natural head position. A radiographic analysis was made using a NEMOTEC software: 13 variables were registered: age, gender, ANB angle (to classify sagittal skeletal relationships) and 10 variables related to craniocervical posture: cervical lordosis, hyoid triangle, craniocervical angle, intervertebral spaces: C0-C1, C1-C2 and distances NSL-Ver, NLVer, ML-Ver, OPT-Hor, CVT-Hor. To evaluate the reliability of measures, 15 randomly selected radiographs were re-measured by the same investigator two weeks after the initial analysis. Results: Intra-class correlation coefficients were in a range of 0.945-0.996. Lordosis, CCA, C1-C2, OPT-Hor y CVT-Hor, values were higher in male than in female children (p<0.05). No statistically significant differences were found among groups of sagittal skeletal relationships, but class III children had a tendency to higher craniocervical flexion; 66.3% of the studied group presented rectified lordotic curvature and class II subjects presented increased values of NSL-Ver, NL-Ver and MLVer. Class I children had the lowest values for OPT-Hor and CVT-Hor. Conclusion: All craniocervical postural variables were higher in boys than in girls. No differences were found in this study between cervical postural variables with different malocclusion. © 2017, Association of Support to Oral Health Research (APESB). All Rights Reserved.